(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2020)
In this paper, the drawability of two-layer (steel-brass) sheets to produce square cup, is investigated through numerical simulations, and experimental tests. Each material has its own benefits and drawbacks in terms of its physical, chemical and mechanical properties, so that the point of this investigation is taking the benefits of different materials, like (low density, high strength and resistibility of corrosion), at the same time and in a one part. ANSYS18 software is used to simulate the deep drawing process of laminated sheet. The deep drawing processes for square cup were carried out under various blank holder loads with different lubrication conditions (dry and lubricant) and with variable layer arrangement. The materials were low carbon steel st1008 and brass CuZn30 sheets with thickness of 0.5mm0and 0.58mm respectively. The thickness of laminated sheet blank was 1.1 mm and its diameter was 83 mm. The drawn cups with less imperfections and satisfactory thickness distribution were formed in this study. It is concluded the greatest thinning appear in the corner of the cup near the punch radius due to extreme stretching take place in this area. Experimental forming load, blank holder load, and thickness distribution are compared with simulation results. Good agreement between experimental and numerical is evident.